Krisis Etika dalam Persaingan Usaha: Mengurai Faktor Pendorong Praktik Penyimpangan di Sektor Bisnis - Zulfa Rahmatilah (Indo Publishing, 2025)
This study examines the ethical crisis emerging within business competition in Indonesia by analyzing three dominant forms of unethical practices: bribery, destructive price competition, and quality cheating. The findings reveal that bribery occurs not only as an individual moral failure but as a systemic response to weak governance and insufficient oversight mechanisms, allowing transactional practices to shape business–bureaucracy relations. Destructive price competition demonstrates that extreme pricing strategies can distort market structure, suppress small business resilience, and intensify the concentration of market power among dominant firms. Meanwhile, quality cheating arises when producers face pressure to reduce production costs and compete in markets that reward low price over quality and compliance, leading to the spread of substandard or mislabeled products. Together, these practices illustrate that the ethical crisis in Indonesia’s business ecosystem is driven by structural pressures rather than isolated misconduct. The study concludes that strengthening regulatory enforcement, improving governance integrity, and enhancing the ethical capacity of businesses particularly SMEs are crucial for ensuring fair, inclusive, and sustainable competition.